Validity of First-Time Diagnoses of Inherited Ichthyosis in the Danish National Patient Registry and the Danish Pathology Registry - Kristensen MH; Schmidt SAJ; Kibsgaard L; Hove H; Sommerlund M; Koppelhus U (Clinical Epidemiology, 2020)
Mattias Hedegaard Kristensen,1 Sigrun Alba Johannesdottir Schmidt,2 Line Kibsgaard,1 Hanne Hove,3 Mette Sommerlund,1 Uffe Koppelhus1 1Department of Dermatology, Aarhus University Hospital, Aarhus, Denmark; 2Department of Clinical Epidemiology, Aarhus University Hospital, Aarhus, Denmark; 3Centre for Rare Diseases, Copenhagen University Hospital, Copenhagen, DenmarkCorrespondence: Uffe KoppelhusDepartment of Dermatology, Aarhus University Hospital, F3, Plan 2,202,Palle Juul-Jensens Boulevard 99, DK 8200, DenmarkTel +45 2494 6245Fax +45 7846 1860Email Uffekopp@rm.dkPurpose: Inherited ichthyosis is a monogenetic disease characterized by hyperkeratosis and scaling of the skin, with large interindividual variation in severity. It can affect quality of life for patients and their families. Population-based data on inherited ichthyosis are lacking, which hampers studies into its epidemiology.Patients and Methods: Based on medical record review, we validated diagnoses of inherited ichthyosis in two nationwide population-based registries commonly used for epidemiological research: The Danish National Patient Registry and the Danish Pathology Registry. The study period was January 1, 1977, through December 31, 2015. Validation samples were taken from one regional hospital without a specialized dermatological department and two specialized dermatological departments. Positive predictive values (PPVs) were estimated overall and for each coding system (ICD-8, ICD-10 and SNOMED), including for specific ICD-10 codes.Results: We identified 1772 first-time diagnoses of inherited ichthyosis; 363 patients were diagnosed at the departments selected for validation, and 307 of these patients (84.6%) had medical records enabling validation. We observed an overall PPV of 73.3% (95% CI: 68.1– 77.9). For ICD-8, ICD-10, and SNOMED diagnoses, the PPVs were 73.2% (95% CI: 58.1– 84.3), 74.7% (95% CI: 69.0– 79.7), and 46.2% (95% CI: 22.1– 71.7), respectively. In analyses for ICD-10 diagnoses, we observed much higher validity of diagnoses from the specialized departments (PPV 79.7%; 95% CI: 74.1– 84.3) than the regional hospital (PPV 5.9%; 95% CI: 0.6– 24.3). The PPVs for specific diagnoses were 80.1% for ichthyosis vulgaris and 96.6% for X-linked ichthyosis but below 45% for remaining, rarer, subtypes.Conclusion: The PPV of first-time diagnosis of inherited ichthyosis made at specialized dermatological departments in the Danish National Patient Registry is approximately 80%. Diagnoses from the Danish Pathology Registry had low PPVs precluding their use for research.Keywords: Denmark, diagnosis, ichthyosis, health administrative data, registration, validity